The Influence of Affective Commitment, Job Satisfaction and Job Stress, on Turnover Intention With Job Security as a Moderating Variable in Retail Employees - Nur Anggraeni, Citra; Puspitaloka Mahadewi, Erlina (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the influence of affective commitment, job satisfaction, and job stress on Turnover Intention, with Job Security as a moderating variable. This study uses a quantitative approach with a survey method. The research sample consisted of 184 permanent retail employees in the Greater Jakarta area. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results showed that job satisfaction had a significant negative effect on Turnover Intention, so the second hypothesis (H2) was accepted. Job stress had a significant positive effect on Turnover Intention, so the third hypothesis (H3) was accepted. Affective commitment did not show a significant effect on Turnover Intention, so the first hypothesis (H1) was rejected. In testing the moderation effect, Job Security did not moderate the relationship between affective commitment and Turnover Intention, so the fourth hypothesis (H4) was rejected. Job Security was proven to moderate the relationship between job satisfaction and Turnover Intention, so the fifth hypothesis (H5) was accepted. Furthermore, job security was also shown to moderate the relationship between job stress and turnover intention, thus accepting the sixth hypothesis (H6). The findings of this study indicate that job satisfaction, job stress, and perceived job security play a significant role in shaping turnover intention. Practically, retail organizations need to consider psychological factors and job stability as part of their employee retention strategies